The Role of Teachers in Overcoming Difficulties in Learning to Read: Writing and Counting Elementary School Students - Salmia Salmia (Universitas Pendidikan Indonesia (UPI), 2020)
The purpose of this study concerns (1) the role of the teacher in identifying students who have difficulty learning to read, write and count; (2) after the student data is identified, it can be seen the factors that cause students to have difficulty learning to read, write and count; (3) for that the teacher has a role in overcoming difficulties in learning to read, write and count. This type of research is descriptive qualitative. Data were collected through interviews, observation and documentation. This study uses data analysis techniques, which consist of the stages of data collection, data reduction, data presentation and drawing conclusions, while the validity of the data is done by checking the results of interviews, data sources and implementation time. The results of the research conducted by grade 1 teachers were (1) identifying learning difficulties by analyzing the results of learning tests, basic ability tests, a scale of disclosing attitudes and learning habits, and observations during the teaching and learning process; (2) Factors that cause difficulties in learning to read, write and count are internal factors, external factors and learning approach factors. These three factors can influence the individual process so as to determine the quality of learning outcomes; (3) the role of the teacher in overcoming learning difficulties in grade 1 students is by guiding, educating, training, and assessing (2) Factors that cause difficulties in learning to read, write and count are internal factors, external factors and learning approach factors. These three factors can influence the individual process so as to determine the quality of learning outcomes; (3) the role of the teacher in overcoming learning difficulties in grade 1 students is by guiding, educating, training, and assessing (2) Factors that cause difficulties in learning to read, write and count are internal factors, external factors and learning approach factors. These three factors can influence the individual process so as to determine the quality of learning outcomes; (3) the role of the teacher in overcoming learning difficulties in grade 1 students is by guiding, educating, training, and assessing